Analisis Ngaji Online Gus Baha Pada YouTube Santri Gayeng: Telaah Retorika Aristoteles - Kastolani, Kastolani; Azwar, Azwar; Damayanti, Damayanit (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padngsidimpuan, 2025)
This study aims to analyze the dynamics of Gus Baha's online lecture on the Santri Gayeng YouTube channel, as well as evaluate the response and impact on netizens using Aristotle's rhetorical theory (ethos, patos, and logos). The research method used is qualitative analysis with data collection techniques through content observation, digital documentation, and literature review related to digital da'wah and religious rhetoric. The Santri Gayeng channel was chosen because it has the largest number of followers among other channels that broadcast Gus Baha's lectures, so it is considered representative in describing the pattern of public acceptance. The results of the study show that Gus Baha's online lecture functions as a means of religious refreshment for the digital society, facilitates understanding of the science of the Qur'an and Hadith, and creates a humanistic and inclusive da'wah space. Gus Baha's rhetorical strategy that stands out through the power of ethos (scientific authority), patos (emotional closeness), and logos (rational argumentation) makes his da'wah easily accepted by various circles. The da'wah that he conveyed did not attack other groups with different views, so that it was able to reach audiences across sects and backgrounds. These findings confirm that online lectures are not only a new alternative in religious learning, but also play an important role in strengthening religious moderation in digital public spaces. This study also contributes to the digital da'wah literature by showing how charismatic scholars use new media to build religious communication that is more relevant to the needs of contemporary society.